Maternal Autonomy Support and Intrusive Control in the United States and China: Moment-to-Moment Associations With Preschoolers' Agency and Defeat. - Chen, Xi; McElwain, Nancy L.; Pomerantz, Eva M.; Wang, Mengjiao (Developmental Psychology, 2024)
This study examines the moment-to-moment within-person associations between maternal and child behaviors during a challenging puzzle task and compares these associations between mother–child dyads from the United States (n = 99, 52 boys, M = 56.05 months, SD = 6.44) and China (n = 101, 46 boys, M = 57.41 months, SD = 6.58). Maternal autonomy support and intrusive control and child agency and defeat were rated in 15-s intervals by native and bicultural coders. Country was examined as a moderator of the moment-to-moment within-person associations between maternal and child behaviors. The results showed that for both U.S. and Chinese dyads, increases in maternal intrusive control predicted subsequent decreases in child agency, and increases in child defeat predicted subsequent increases in maternal autonomy support. Furthermore, increases in maternal autonomy support predicted subsequent increases in child defeat, but for the Chinese dyads only. Public Significance Statement: This study examined how maternal and child behaviors change in response to each other during a challenging puzzle task among U.S. and Chinese dyads. For both U.S. and Chinese preschoolers, children's eagerness and confidence to complete the task decreased immediately after mothers exerted more intrusive control. Additionally, Chinese preschoolers, but not U.S. preschoolers, expressed more defeat and negative emotion immediately after mothers provided more support of the child's autonomy. The findings showed both cultural similarities and differences in the real-time dynamics of mother–child interaction.